Numerical Investigation Of Flow And Heat Transfer In Microchannel - Mustafa, Ahmad Khusaire (2018)
A numerical study was conducted to investigate the flow of water flowing through a rectangular channel with a hydraulic diameter of 86.58 μm.A constant heat flux is applied to the heatsink top surface to investigate the cooling performance of the microchannel heatsink.The flow employed had Reynolds numbers between 140 to 1400.It was observed that within the aforementioned Reynolds number range,the water flows in laminar regiment.As the inlet velocity increased,the velocity profile took a longer path to develop.The effect of increasing Reynolds number also increased the localised Nusselt number and lowered the wall and fluid bulk temperatures.Substitution of water with Ag-H2O 0.5 wt% nanofluid resulted in better overall heat transfer performance in terms of wall temperature and Nusselt number.At